Revitalizing The Da‘Wah of Wali Songo - Arifin, Samsul; As’ad, As’ad (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study addresses the complex social challenges of the Society 5.0 era, such as inequality and the crisis of trust, by examining the role of local wisdom in maintaining global cohesion. Focusing on the Indonesian context, the research explores the thought of K.H.R. As‘ad Syamsul Arifin in Tarikh Perjuangan Islam Indonesia, specifically his interpretation of the Wali Songo’s culture-based da‘wah strategies. The objective is to identify character traits and social harmony strategies relevant to building an inclusive modern civilization. Utilizing Hans-Georg Gadamer’s philosophical hermeneutics, the study analyzes the text within its historical and cultural horizons, supported by data triangulation with literature on Nusantara Sufism and Islamic education. Findings indicate that the Wali Songo integrated spiritual depth—marked by wara‘ and tawadhu‘—with socio-political competence, enabling an adaptive and peaceful expansion of Islam. Their harmony strategies included moral exemplarity, collective deliberation, and the establishment of pesantren as centers for community building. The study concludes that revitalizing these Sufi values and the da‘wah bil-irsyad model serves as a vital bridge between local wisdom and global harmony, offering a sustainable, inclusive framework for navigating the sociocultural tensions of the contemporary era.